GENE-37. VESTIBULAR SCHWANNOMA IS COMPRISED OF NEURAL CREST AND IMMUNE SUBGROUPS. (11th November 2019) - John Liu, S; Vasudevan, Harish; Pekmezci, Melike; Choudhury, Abrar; Lien, Brian; Breshears, Jonathan; Swaney, Danielle; Magill, Stephen; Lang, Ursula; Chen, William; Gopinath, Chetna; Castro, Maria; et al.
Abstract: BACKGROUND: Vestibular schwannomas (VS) are tumors arising from cranial nerve Schwann cells and show variable outcomes after treatment, including oscillation in size for many years after radiosurgery. To understand the unique biology of VS, we performed multiplatform molecular profiling to develop a single cell atlas of VS and reveal that VS exists on a molecular axis defined by neural crest and immune genes. METHODS: Sixty-six sporadic VS with available tissue for molecular profiling from 59 consecutive patients at a single institution were included. 850K DNA methylation arrays and RNA sequencing were used to profile both primary (76%) and recurrent (24%) tumors. Single nuclei RNA sequencing of 7 tumors and single cell RNA sequencing of 3 tumors and cell lines were used to define the cellular composition of VS and heterogeneous changes in molecular programs following irradiation. Molecular subtyping was performed by hierarchical clustering of differentially-methylated DNA probes and validated using transcriptomic data. Mechanistic experiments were performed using cultured human schwann cells and human vestibular schwannoma cells, confocal microscopy, CRISPR interference, proteomic mass spectrometry and lymphocyte migration assays. RESULTS: Multiplatform genomic profiling and machine learning revealed that VS is comprised of two distinct molecular subtypes characterized by heterogeneous cell populations. Neural crest enriched VS express primary cilia and are associated with misactivation of the Hedgehog pathway. Consistently, we find that the Hedgehog pathway antagonist vismodegib blocks the growth of human Schwann cells. Irradiation epigenetically reprograms tumors and cell lines to reduce ciliary length, attenuate Hedgehog signaling, activate senescence pathways, and express cytokines and apolipoproteins that recruit lymphocytes and macrophages to immune enriched VS. CONCLUSIONS: Our data reveal novel molecular subtypes of VS and establish a framework for understanding how irradiation modifies the epigenome and tumor microenvironment.